Feasibility and potential effectiveness of an intensive trauma-focused treatment programme for families with PTSD and mild intellectual disability. Issue 1 (31st December 2020) - Mevissen, Liesbeth; Ooms-Evers, Marjolein; Serra, Marike; de Jongh, Ad; Didden, Robert
ABSTRACT: Background: Persons with mild intellectual disabilities or borderline intellectual functioning (MID-BIF; IQ 50–85) have a higher risk of being exposed to traumatic events and developing posttraumatic stress disorder (PTSD). EMDR therapy has shown to be applicable, safe and potentially effective for the treatment of PTSD in individuals with MID-BIF. However, in traumatized multi-problem families with MID-BIF and (impending) out of home placement of children, standard PTSD treatment in an outpatient setting may not be appropriate. Objective: To evaluate the feasibility and potential effectiveness of KINGS-ID, a six-week clinical trauma-focused treatment programme consisting of intensive EMDR therapy with parents and children, and parental skills training followed by two weeks of parent support at home. Method: Six families (nine parents of whom six had MID-BIF) and 10 children (all having MID-BIF) participated in the KINGS-ID programme. Seven parents and seven children had PTSD. Data were collected within a single case study design. For each family member data were collected during baseline (three measurements), treatment (seven weekly measurements), posttreatment (three measurements) and at follow-up (three measurements). Results: None of the family members dropped out. Within the first two treatment weeks all but one child and one parent no longer met PTSD symptom criteria. In both children and parents, trauma-related symptoms and daily life impairment significantly decreased following treatment and in parents a significant decrease in symptoms of general psychopathology and parental stress was found. Results were maintained at six-month follow-up. Conclusions: The findings of the current study are promising given that the treatment programme seems to offer new perspectives for traumatized multi-problem families with MID-BIF.